Probiotic-Containing Nanofiber-Based Dental Floss Suppresses Subgingival Red Complex Periopathogens: A Randomized Double-Blind Crossover Trial - Filip Hromcik; Pavla Holochova; Jan Bohm; Eva Kuzelova Kostakova; Zdenek Pokorny; Filip Ruzicka; Petra Borilova Linhartova (Probiotics and Antimicrobial Proteins, 2026)
Recently, a dental nanofloss containing a probiotic ( Ligilactobacillus salivarius ; LS -nanofloss) was developed by our team. This study aimed to evaluate: (i) its impact on subgingival plaque accumulation and gingival bleeding, and (ii) retention of selected subgingival periopathogens and the introduced probiotic bacteria, and (iii) its effect on the quantity of red complex periopathogens in the subgingival environment. This randomized, double-blind, crossover trial was conducted in 30 healthy male participants. Each subject underwent professional flossing and subsequently used LS -nanofloss/probiotic-free (control) nanofloss at two separate 14-day periods, always followed by a 14-day wash-out. Clinical assessments (subgingival plaque accumulation and gingival bleeding) were performed at five time points; subgingival plaque samples were collected at seven time points for quantitative analysis of total bacterial DNA, L. salivarius , a cariogenic bacterium Streptococcus mutans , and red complex periopathogens. Both nanofloss types significantly reduced plaque accumulation and gingival bleeding after 14 days ( p < 0.05), especially in the anterior regions; these improvements, however, regressed after the wash-out period. L. salivarius DNA was detected in 93.3% of samples after professional flossing, 36.7% after self-flossing, and 13.3% even after the wash-out period. The use of LS -nanofloss was associated with a significant reduction in red complex periopathogens ( p < 0.05). The investigated L. salivarius -containing nanofloss proved to be an effective oral hygiene device for subgingival introduction of this probiotic strain. Its application reduced the relative quantity of red complex periopathogens in the subgingival environment, showing potential to prevent the development of periodontitis. The trial was registered retrospectively on 2/9/2025 as NCT07149493.

Phylogenetic community ecology of soil biodiversity using mitochondrial metagenomics - Carmelo Andújar; Paula Arribas; Filip Ruzicka; Alex Crampton‐Platt; Martijn J.T.N. Timmermans; Alfried P. Vogler (Molecular Ecology, 2015)
High‐throughput DNA methods hold great promise for the study of taxonomically intractable mesofauna of the soil. Here, we assess species diversity and community structure in a phylogenetic framework, by sequencing total DNA from bulk specimen samples and assembly of mitochondrial genomes. The combination of mitochondrial metagenomics and DNA barcode sequencing of 1494 specimens in 69 soil samples from three geographic regions in southern Iberia revealed >300 species of soil Coleoptera (beetles) from a broad spectrum of phylogenetic lineages. A set of 214 mitochondrial sequences longer than 3000 bp was generated and used to estimate a well‐supported phylogenetic tree of the order Coleoptera. Shorter sequences, including cox1 barcodes, were placed on this mitogenomic tree. Raw Illumina reads were mapped against all available sequences to test for species present in local samples. This approach simultaneously established the species richness, phylogenetic composition and community turnover at species and phylogenetic levels. We find a strong signature of vertical structuring in soil fauna that shows high local community differentiation between deep soil and superficial horizons at phylogenetic levels. Within the two vertical layers, turnover among regions was primarily at the tip (species) level and was stronger in the deep soil than leaf litter communities, pointing to layer‐mediated drivers determining species diversification, spatial structure and evolutionary assembly of soil communities. This integrated phylogenetic framework opens the application of phylogenetic community ecology to the mesofauna of the soil, among the most diverse and least well‐understood ecosystems, and will propel both theoretical and applied soil science.

Usefulness of McRAPD for typing and importance of biofilm production in a case of nosocomial ventriculoperitoneal shunt infection caused by Candida lusitaniae - Petr Hamal; Juraj Hanzen; Frantisek Horn; Jitka Trtkova; Lenka Ruskova; Renata Vecerova; Filip Ruzicka; Anna Vollekova; Vladislav Raclavsky (Folia Microbiologica, 2011)